Fratura vertebral e HIV: revisão sistemática e metanálise - Ilha, Thales Augusto de Santa Helena (2017)
The survival of HIV-infected patients has increased with the advent of antiretroviral therapy. Consequently, comorbidities uncommon in these population emerged and the skeleton is one o f systems affected. Vertebral fracture is a sign of reduction in bone quality and a hallmark of osteoporosis. This study aims to assess the frequency of spine fractures in HIV-positive men and women aged over 18 years. We performed a systematic review of randomized controlled trials (RCTs), cohort studies, cross-sectional studies, and case-control studies. The study protocol is registered with the International Prospective Register of Systematic Reviews (PROSPERO) under the number CRD42016048702. Studies that have evaluated either morphometric or clinical vertebral fracture were included. The search strategy included the following descriptors: "Spinal Fractures"; "Fractures, Bone"; "HIV"; "Acquired Immunodeficiency Syndrome"; and "Anti-Retroviral Agents" in the databases PubMed, BIREME, EMBASE, and the Cochrane Library. Additionally, some studies were selected from the reference lists of the included articles. We considered studies written in any language and with no publication date limits. Two protocol members independently performed the selection of the studies. Also, two research members also performed the data extraction, separately. Afterward, it was discussed and agreed between both. In total 488 studies were found, of which 90 were excluded due overlap. After the title and abstracts screening, 53 studies remained. Of these, 28 were excluded due to lack of outcome, study design, and redundant publication. A total of 102.744 individuals HIV positive were identified at 26 studies. The metanalysis of the prevalence of vertebral fractures included 14 studies with 10.593 subjects. The prevalence was 12.7% (CI 5.6% to 26.4%). Besides, when we evaluated independently clinical vertebral fracture (n = 5) and morphometric vertebral fracture (n=9), the prevalence was 3.9% (95%CI 0.9% to 15.8%) and 21,1% (95%CI 14,1% to 30.4%) respectively. The metanalysis of the incidence of vertebral fractures included 10 studies with 430589 individuals. The incidence was 0.8 (95% CI 0.4 to 1.8) per 1000 personyears. There was no study of incidence evaluating morphometric fractures. In 9 studies, 56117 HIV-infected patients were compared with 5171132 HIV-uninfected controls. The HIVinfected patients had an odds ratio of 2.3 (95% CI 1.37 to 3.85) when compared with HIVuninfected patients. We did not find association between age and gender and prevalence of vertebral fracture in HIV. In conclusion, the frequency of morphometric vertebral fractures is high in HIV-subjects. Moreover, HIV-positive subjects had a higher chance of vertebral fractures when compared with HIV-negative subjects.